High-thermal-conductivity and low-dielectric heat-conducting gasket and preparation method thereof
By introducing active functional groups through plasma treatment of boron nitride powder, the problem of difficult to improve the thermal conductivity coefficient of the thermal conductivity gasket is solved, and the combination of high thermal conductivity and low dielectric properties is achieved, meeting the application needs of 5G, 6G communications and other applications.
Patent Information
- Application Number
- CN202411785619.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-20
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
While existing thermal conductivity gaskets meet high thermal conductivity and low dielectric properties, it is difficult to improve the thermal conductivity coefficient, and the two-dimensional characteristics of boron nitride and surface inertia make it difficult to add it to the system.
By modifying the boron nitride powder, the active functional groups are introduced by low-temperature plasma treatment, and a firm chemical bond is formed with a powder modifier with good compatibility with the resin system, which greatly improves the addition of boron nitride in the polymer system.
The thermal conductivity coefficient is increased to 6.0W/mK, and the dielectric constant reaches 3.0 at 1MHz frequency, meeting the needs of high thermal conductivity and low dielectric properties, and increasing the amount of boron nitride added to the system.
Smart Images

Figure BDA0005173962310000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive interface materials, and in particular relates to a thermal conductive gasket with high thermal conductivity and low dielectric constant and a preparation method thereof. Background Art
[0002] With the development of wireless communications and the advent of the 5G and 6G eras, the signal transmission rate is getting faster and faster, the number of connected terminal devices is increasing, the response speed and operating frequency of base stations are getting faster and faster, and the chip temperature will only get higher and higher. The rapid and timely heat removal is a guarantee of the working life and working stability of the base station. At the same time, the biggest advantage of 5G and 6G communications is the fast transmission speed, and the biggest disadvantage is the poor penetration and large attenuation. Therefore, 5G requires the dielectric constant and dielectric loss of the propagation medium material to be small, and to remain stable over a wide frequency range. In particular, the application of wireless communications in new energy vehicles and autonomous driving has extremely high requirements for signal speed and delay, and extremely high requirements for the working stability and reliability of the equipment. Summary of the invention
[0003] In view of the above-mentioned prior art, the present invention provides a high thermal conductivity and low dielectric thermal conductive gasket and a preparation method thereof. The specific technical scheme is as follows:
[0004] The first object of the present invention is to provide a thermally conductive pad with high thermal conductivity and low dielectric constant, comprising the following components in parts by weight:
[0005] 3-6 parts of vinyl silicone oil; 0.5-2 parts of hydrogenated silicone oil; 0.1-0.5 parts of catalyst; 0.1-0.5 parts of inhibitor; 70-90 parts of modified boron nitride; 10-20 parts of zinc oxide;
[0006] The modified boron nitride is obtained by treating 0.3-2 parts of a powder modifier with a discharge plasma;
[0007] The powder modifier is one or more of hydroxy vinyl silicone oil, hydroxy silicone oil, hydrogen silicone oil, dodecyl trimethoxy silane, A-151, A-171, and ethyl orthosilicate.
[0008] In order to meet both high thermal conductivity and low dielectric properties, the selection of fillers in thermally conductive gaskets is key. By screening common powders such as alumina and aluminum nitride, although the thermal conductivity is also high, the dielectric constant is also relatively high, and boron nitride (BN) is an ideal filler with high thermal conductivity and low dielectric, with a thermal conductivity of up to 80W / mK, and a dielectric constant usually between 1.9 and 3.8, depending on temperature, frequency and crystal orientation. The more mature BN with a thermal conductivity of 70W / mK and a dielectric constant of 2.2 is selected as the main filler, filled into the organosilicon hydrosilane addition system, calendered and cured, to prepare a high thermal conductivity and low dielectric thermal conductive gasket. However, due to the two-dimensional characteristics of boron nitride, the powder structure is flaky, and the specific surface area is much larger than that of spherical or granular powders; in addition, the upper and lower surfaces of BN are extremely inert, and there are only a small number of functional groups on the four sides. Therefore, it is difficult to add a large amount, which makes it difficult to improve the thermal conductivity.
[0009] The present invention modifies boron nitride powder and greatly increases the addition of BN in the system, so that the thermal conductivity can reach as high as 6W / mK and the dielectric constant can reach 3.0 at a frequency of 1MHz.
[0010] Principle of boron nitride powder modification: Due to the surface inertness of boron nitride and the extremely low content of surface functional groups, powder modifiers such as coupling agents cannot be chemically bonded to the powder surface. The oil absorption value in silicone resin is very high and the compatibility with the system is poor. Therefore, the key to powder modification is to connect the functional groups to the surface of boron nitride powder and then react with the powder modifier. The present invention utilizes the characteristics of low-temperature plasma (plasma), where electrons and ions are in equilibrium. The temperature of electrons can be very high, but the temperature of heavy particles such as ions, molecules and atoms is very low. The high energy of electrons can excite, ionize and decompose the molecules of an object, and can also keep the reaction container at a low temperature or even room temperature. The surface of the material treated by plasma undergoes a variety of chemical and physical changes, and active functional groups such as hydroxyl, carboxyl, carbonyl, amine, etc. are introduced on the surface of the material through the dissociation and reaction of gases. The introduced functional groups depend on the gas in the plasma chamber. The surface of the material is usually treated by plasma discharge under oxygen or air. The high-energy particles of plasma are used to bombard the surface, break the covalent bonds, and form free radicals on the surface of the material. These free radicals can react with oxygen atoms and ammonia atoms ionized in the plasma atmosphere to form various active functional groups on the surface.
[0011] Furthermore, the preparation method of the modified boron nitride comprises the following steps:
[0012] a. Place the boron nitride powder in a vacuum drum plasma device and extract the air in the cavity by vacuum;
[0013] b. Discharge plasma treatment is adopted, the rotation speed is 20-40rpm, and the treatment time is 10-30min;
[0014] c. Add 0.15-1.0 parts of powder modifier, add vacuum, discharge plasma treatment, speed of 20-40rpm, treatment time of 20-40min;
[0015] d. Add 0.15-1.0 parts of powder modifier, add vacuum, rotate at 20-40 rpm, process for 20-40 min, and discharge to obtain the modified boron nitride.
[0016] Furthermore, the modified boron nitride includes 60-70 parts of 1# modified boron nitride with different particle sizes and 10-20 parts of 2# modified boron nitride.
[0017] The present invention adopts modified boron nitride with different particle sizes to make products with higher thermal conductivity. Small particles can fill the gaps between large particles, and the thermal conductivity is better.
[0018] Furthermore, the particle size of the 1# modified boron nitride is 10-20 μm, preferably 15 μm; the particle size of the 2# modified boron nitride is 1-5 μm, preferably 4 μm.
[0019] Furthermore, the medium gas for the discharge plasma treatment is one or two of oxygen (O2), argon (Ar), air, nitrogen (N2), and water vapor (H2O), preferably O2.
[0020] Furthermore, in the modified boron nitride preparation method, the powder modifier in step c is hydroxy vinyl silicone oil, and the powder modifier in step d is dodecyltrimethoxysilane. Preferably, the mass ratio of the powder modifier to hydroxy vinyl silicone oil and dodecyltrimethoxysilane is 1:1.
[0021] Furthermore, the vinyl silicone oil has a viscosity of 100 mPa·s and a vinyl content of 0.4 mmol / g.
[0022] Furthermore, the hydrogen-containing silicone oil has a viscosity of 50 mPa·s and a hydrogen content of 1.2 mmol / g.
[0023] Furthermore, the catalyst is a platinum catalyst, and the inhibitor is alkynyl cyclohexanol.
[0024] Furthermore, the particle size of the zinc oxide is 0.5-10 μm, more preferably 0.8-5 μm, and more preferably 1 μm.
[0025] The second object of the present invention is to provide a method for preparing the above-mentioned thermally conductive gasket with high thermal conductivity and low dielectric constant, comprising the following steps:
[0026] 1) Add vinyl silicone oil, hydrogen silicone oil, inhibitor, modified boron nitride and zinc oxide into a planetary gravity dispersion device, stir for 1-5 minutes at a rotation speed of 800-1000 rpm and a vacuum degree of less than -0.09 MPa;
[0027] 2) After scraping the wall, cool to room temperature, add catalyst, put into the planetary gravity dispersion equipment again, and stir for 1-5 minutes at a speed of 800-1000rpm and a vacuum degree of less than -0.09MPa;
[0028] 3) After calendering, the heat is cured to obtain the thermally conductive gasket with high thermal conductivity and low dielectric constant.
[0029] Furthermore, the thickness of the calendering molding in step 3) is 0.3-5 mm.
[0030] The beneficial effects of the present invention are:
[0031] The present invention innovatively uses high-energy particles in a plasma atmosphere to bombard the powder surface and react. After introducing active functional groups on the material surface through gas dissociation and reaction, a powder modifier with good compatibility with the resin system is used to form a strong chemical bond with the powder surface functional groups to complete the modification, which greatly improves the addition of boron nitride to the polymer system. The thermal conductivity of the thermally conductive gasket of the present invention can reach 6.0w / mk, and the dielectric constant can reach 3.0. Its high thermal conductivity can conduct the heat generated by electronic components in time to ensure the working stability of electronic components; its ultra-low dielectric constant is applied to 5G and 6G communications, with little effect on signal transmission speed and signal delay, and high signal fidelity. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] Example:
[0034] A preparation method of a thermally conductive gasket with high thermal conductivity and low dielectric constant comprises the following steps:
[0035] 1. Preparation of modified boron nitride:
[0036] 1.1# Preparation of modified boron nitride:
[0037] a. By weight, 61.74 parts of boron nitride powder having a particle size of 15 μm were placed in a vacuum drum plasma device, and the air in the cavity was evacuated by vacuum;
[0038] b. Use oxygen as the medium gas, discharge plasma treatment, rotation speed 30rpm, treatment time 20min;
[0039] c. Add 0.63 parts of hydroxy vinyl silicone oil, add vacuum, continue to treat with O2 plasma, and rotate at 30rpm for 30min;
[0040] d. Add 0.63 parts of dodecyltrimethoxysilane, apply vacuum, rotate at room temperature and 30 rpm for 60 minutes, and the material is 1# modified boron nitride.
[0041] 2.2# Preparation of modified boron nitride:
[0042] The boron nitride powder is 14.7 parts of boron nitride powder with a particle size of 4 μm. In step c, 0.15 parts of hydroxy vinyl silicone oil are added. In step d, 0.15 parts of dodecyltrimethoxysilane are added. The other steps are the same as those in the preparation method of 1# modified boron nitride and will not be repeated here.
[0043] 2. Preparation of thermally conductive gasket with high thermal conductivity and low dielectric
[0044] 1) By weight, 4.0 parts of vinyl silicone oil, 0.7 parts of hydrogenated silicone oil, 0.1 parts of inhibitor alkynyl cyclohexanol, 63.0 parts of 1# modified boron nitride, 15 parts of 2# modified boron nitride and 16 parts of zinc oxide with a particle size of 1 μm are added to a planetary gravity dispersion device, and stirred for 2 minutes at a rotation speed of 900 rpm and a vacuum degree of less than -0.09 MPa; wherein the vinyl silicone oil has a viscosity of 100 mPa·s and a vinyl content of 0.4 mmol / g; the hydrogenated silicone oil has a viscosity of 50 mPa·s and a hydrogen content of 1.2 mmol / g.
[0045] 2) After scraping the wall, cool to room temperature, add 0.2 parts of platinum catalyst, put it into the planetary gravity dispersion equipment again, and stir for 2 minutes at a speed of 900 rpm and a vacuum degree of less than -0.09 MPa;
[0046] 3) rolling into a 3 mm finished product, heating to 125° C., and curing for 30 minutes to obtain the thermally conductive gasket with high thermal conductivity and low dielectric constant.
[0047] Comparative Example 1:
[0048] Preparation of a thermally conductive pad:
[0049] Compared with the embodiment, "1# modified boron nitride" is replaced by "1# boron nitride", and the 1# boron nitride is a boron nitride powder with a particle size of 15 μm, that is, the 15 μm boron nitride powder is not modified; "2# modified boron nitride" is replaced by "2# boron nitride", and the 2# boron nitride is a boron nitride powder with a particle size of 4 μm, that is, the 4 μm boron nitride powder is not modified; other method steps and other material amounts are the same as those in the embodiment, and will not be repeated here.
[0050] Comparative Example 2:
[0051] Preparation of a thermally conductive pad:
[0052] Compared with the embodiment, "1# modified boron nitride" is replaced by "1# alumina", and the 1# alumina is an alumina powder with a particle size of 15μm; "2# modified boron nitride" is replaced by "2# alumina", and the 2# alumina is an alumina powder with a particle size of 4μm; other method steps and other material amounts are the same as those in the embodiment, and will not be repeated here.
[0053] Comparative Example 3:
[0054] Preparation of a thermally conductive pad:
[0055] Compared with the embodiment, "1# modified boron nitride" is replaced by "1# aluminum nitride", and the 1# aluminum oxide is an aluminum nitride powder with a particle size of 15μm; "2# modified boron nitride" is replaced by "2# aluminum nitride", and the 2# aluminum nitride is an aluminum nitride powder with a particle size of 4μm; other method steps and other material amounts are the same as those in the embodiment, and will not be repeated here.
[0056] The thermal conductive pads prepared in the examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1.
[0057] Thermal conductivity: Equipment: hot disk, Standard: ISO 22007-2;
[0058] Viscosity: Test method: HAAKE rheometer, 1rpm*5min;
[0059] Hardness: Test equipment: shore OO hardness tester, test standard: ASTM D2240;
[0060] Dielectric constant: Test equipment: Dielectric constant tester, test standard: ASTM D150-18.
[0061] Table 1 Performance test results of thermally conductive pads prepared in the embodiments and comparative examples
[0062]
[0063] From the test results in Table 1, it can be seen that compared with the modified boron nitride, the untreated boron nitride cannot add all the fillers and cannot be made into a finished product; aluminum oxide can be added relatively well, but the thermal conductivity is 16% lower and the dielectric constant is nearly 50% higher; although the thermal conductivity of aluminum nitride is good and slightly higher, the dielectric constant is still nearly 50% higher. In summary, the present invention uses modified boron nitride to fill and prepare high thermal conductivity and low dielectric thermal conductive gaskets to meet the popularization and application needs of wireless communications such as 5G and 6G, and its suitable cost will meet the future development trend.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A thermally conductive gasket with high thermal conductivity and low dielectric constant, characterized in that: The composition comprises the following components in parts by weight: 3-6 parts of vinyl silicone oil; 0.5-2 parts of hydrogenated silicone oil; 0.1-0.5 parts of catalyst; 0.1-0.5 parts of inhibitor; 70-90 parts of modified boron nitride; 10-20 parts of zinc oxide; The modified boron nitride is obtained by treating 0.3-2 parts of a powder modifier with a discharge plasma; The powder modifier is one or more of hydroxy vinyl silicone oil, hydroxy silicone oil, hydrogen silicone oil, dodecyl trimethoxy silane, A-151, A-171, and ethyl orthosilicate.
2. The high thermal conductivity and low dielectric thermal conductive pad according to claim 1, characterized in that: The preparation method of the modified boron nitride comprises the following steps: a. Place the boron nitride powder in a vacuum drum plasma device and remove the air in the cavity by vacuum; b. Discharge plasma treatment is adopted, the rotation speed is 20-40rpm, and the treatment time is 10-30min; c. Add 0.15-1.0 parts of powder modifier, add vacuum, discharge plasma treatment, speed of 20-40rpm, treatment time of 20-40min; d. Add 0.15-1.0 parts of powder modifier, add vacuum, rotate at 20-40 rpm, process for 20-40 min, and discharge to obtain the modified boron nitride.
3. The high thermal conductivity and low dielectric thermal conductive pad according to claim 1 or 2, characterized in that: The modified boron nitride comprises 60-70 parts of 1# modified boron nitride with different particle sizes and 10-20 parts of 2# modified boron nitride.
4. The high thermal conductivity and low dielectric thermal conductive pad according to claim 3, characterized in that: The particle size of the 1# modified boron nitride is 10-20 μm; the particle size of the 2# modified boron nitride is 1-5 μm.
5. The high thermal conductivity and low dielectric thermal conductive pad according to claim 3, characterized in that: In the modified boron nitride preparation method, the powder modifier in step c is hydroxy vinyl silicone oil, and the powder modifier in step d is dodecyltrimethoxysilane.
6. The high thermal conductivity and low dielectric thermal conductive gasket according to claim 1 or 2, characterized in that: The medium gas for the discharge plasma treatment is one or two of oxygen, argon, air, nitrogen and water vapor.
7. The high thermal conductivity and low dielectric thermal conductive gasket according to claim 1, characterized in that: The vinyl silicone oil has a viscosity of 100 mPa·s and a vinyl content of 0.4 mmol / g; the hydrogen-containing silicone oil has a viscosity of 50 mPa·s and a hydrogen content of 1.2 mmol / g.
8. The high thermal conductivity and low dielectric thermal conductive pad according to claim 1, characterized in that: The catalyst is a platinum catalyst, and the inhibitor is alkynyl cyclohexanol.
9. The high thermal conductivity and low dielectric thermal conductive gasket according to claim 1, characterized in that: The particle size of the zinc oxide is 0.5-10 μm.
10. A method for preparing a thermally conductive gasket with high thermal conductivity and low dielectric constant as claimed in any one of claims 1 to 9, characterized in that: The steps include: 1) Add vinyl silicone oil, hydrogen silicone oil, inhibitor, modified boron nitride, zinc oxide and powder modifier into a planetary gravity dispersion device, stir for 1-5 minutes at a speed of 800-1000 rpm and a vacuum degree of less than -0.09 MPa; 2) After scraping the wall, cool to room temperature, add the catalyst, put it into the planetary gravity dispersion equipment again, and stir for 1-5 minutes at a speed of 800-1000rpm and a vacuum degree of less than -0.09MPa; 3) After calendering, the heat is cured to obtain the thermally conductive gasket with high thermal conductivity and low dielectric constant.